2017
DOI: 10.3892/mmr.2017.7208
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of tribulusamide D isolated from Tribulus terrestris in lipopolysaccharide-stimulated RAW264.7 macrophages

Abstract: Tribulus terrestris (T. terrestris) has been used as a traditional medicine for the treatment of a variety of diseases, including inflammation, edema and hypertension. The aqueous and ethanol extracts of T. terrestris contain alkaloids, flavonoids, tannins, quinines and phenolic compounds. Tribulusamide D is a compound that has been isolated from the ethanol extract of T. terrestris. The present study investigated the anti-inflammatory effect of tribulusamide D on lipopolysaccharide (LPS)-stimulated RAW 264.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Macrophages, as classical innate immune cells, play important roles in maintaining homeostasis such as phagocytizing foreign substances and secreting cytokines in the process of immunoreactivities ( 11 , 12 ). In addition to their classical function in immune system, the non-classical function of macrophage in peripheral, non-lymphoid organs has been widely investigated ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, as classical innate immune cells, play important roles in maintaining homeostasis such as phagocytizing foreign substances and secreting cytokines in the process of immunoreactivities ( 11 , 12 ). In addition to their classical function in immune system, the non-classical function of macrophage in peripheral, non-lymphoid organs has been widely investigated ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammation effect of Tribulus terrestris L. contributes to its effectiveness in multiple diseases while the anti-inflammatory component of Tribulus terrestris L. is not well-known. Lee et al found that tribulusamide D, a compound isolated from Tribulus terrestris L., suppressed LPS-induced inflammatory response in RAW 264.7 cells via inhibition of P38 and NF- κ B signaling cascade [ 13 ]. N-trans- ρ -caffeoyl tyramine, which is also one of the components of Tribulus terrestris L., presented anti-inflammatory activity in LPS-stimulated RAW 264.7 cells by suppression of the protein levels of COX-2 and p-JNK [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tribulus terrestris L. (TT, Zygophyllaceae family), which contains active components including alkaloids, steroidal saponins, flavonoids, tannins, amino acids, quinines, and phenolic compounds, is a commonly used traditional Chinese herbal medicine, also known as Bai Jili in Chinese, for treating various diseases including hypertension, edema, eye problems, sexual dysfunction, and rheumatoid arthritis in clinics for thousands of years [ 13 , 14 ]. The prosexual, cardiac-protective, muscle protective, neuroprotective, and osteoprotective effects of TT were most studied in the recent years [ 14 19 ], and the anti-inflammatory effect of TT might contribute to these broad range of biological effects [ 13 ]. In our previous studies, we have established multiple drug screening models using zebrafish, such as proangiogenesis [ 20 , 21 ], antiangiogenesis [ 22 ], cerebral hemorrhage [ 23 , 24 ], and neuroprotection [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…TT is used for kidney disorders by removing the gravel from the urine and stone in the bladder. [678910]…”
Section: Introductionmentioning
confidence: 99%
“…It has already been proven that TT plant extract has antioxidative, apoptosis inhibitory, and vasodilator properties, as well as protecting renal epithelial cells against damages due to oxalates and ethylene glycol consumption. [78910] The aim of this study was to investigate the protective effects of TT extracts against acute kidney injury (AKI) induced by mercuric chloride.…”
Section: Introductionmentioning
confidence: 99%